Visual imagery vividness declines across the lifespan. (September 2022) - Gulyás, Erzsébet; Gombos, Ferenc; Sütöri, Sára; Lovas, Andrea; Ziman, Gergő; Kovács, Ilona
Abstract: The capacity to elicit vivid visual mental images varies within an extensive range across individuals between hyper- and aphantasia. It is not clear, however, whether imagery vividness is constant across the lifespan or changes during development and later in life. Without enforcing the constraints of strict experimental procedures and representativity across the entire population, our purpose was to explore the self-reported level of imagery vividness and determine the relative proportions of aphantasic/hyperphantasic participants in different age groups. Relying on the frequently used Vividness of Visual Imagery Questionnaire, we collected data on a random sample of 2252 participants between the ages of 12–60 years. We found a novel developmental pattern that describes a declining ability to elicit vivid visual mental images in the group averages of different age groups from adolescence to middle age. This effect involves both a decreasing proportion of individuals with vivid visual imagery vividness and an increasing proportion of individuals with low imagery vividness as maturation (based on bone age assessments in adolescents) and ageing progress. These findings may shed some light on the developmental mechanisms of our internal, stimulus-independent processes, and might also help to determine genetic, maturational, and age-dependent factors in the cases of hyper- and aphantasia.